Factor of the acceptance for QR code payment methods usage among students at University Malaysia Kelantan (UMK) - Ahmad Arif Azwar Anuar; Ahmad Fahmi Izman Mohd Tohir; Aina Nabilah Ahmad; Aini Syazwani Zamri (2024)
The community's way of life has altered significantly since the COVID-19 pandemic, and non-contact payment transactions are one example of this. Users can now make payments more quickly and easily with this expanding payment option. Utilising QR codes during a payment transaction has become commonplace, having started with online payments. The purpose of this study is to elucidate the factors that influence students at Universiti Malaysia Kelantan (UMK) to accept QR code payment methods: attitude, knowledge, and trust. To accomplish the research, an expanded version of the Technology Acceptance Model (TAM) was used. 357 UMK students on the City Campus provided the research data. The results show a significant relationship between each of the three factors and the acceptance of QR code payment methods among student at UMK. Therefore, it is expected that the result of this research will be useful in making inferences for others research with similar characteristics. The study findings suggest that the attitude, knowledge, and trust of students at UMK play a crucial role in their acceptance of QR code payment methods. These factors can be considered when implementing and promoting such payment methods in other educational institutions or organizations with similar characteristics. Additionally, further research could explore strategies to enhance these factors and increase the adoption of QR code payment methods among students.